(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Vitamin D is a micronutrient that plays a critical role in human health; vitamin D has both skeletal and extra skeletal functions. Vitamin D is essential for maintenance of bone and musculoskeletal health. It plays a crucial role in calcium and phosphate homeostasis as well as normal bone growth and mineralization. Although vitamin D, which is an essential fat-soluble nutrient, was first identified as a vitamin, it is now considered a prohormone and is unique to other nutrients because it can be synthesized in the skin through exposure to sunlight. Cutaneous synthesis of vitamin D3 requires the exposure of ultra-violet B rays at wavelength of 290 -315 nm. Once formed, vitamin D3 exits the cutaneous tissue and enters the circulation. Vitamin D is essential for maintenance of bone and musculoskeletal health. It plays a crucial role in calcium and phosphate homeostasis as well as normal bone growth and mineralization. 1,25(OH)2D has been shown to have prodifferentiation and antiproliferation effects on the keratinocyte, anti-tumergenic and anti-metastatic activities on several types of cancer cells, immune-modulatory effects on macrophages and on activated T and B lymphocytes, effects on skeletal muscle function, and protective effects against cardio-metabolic disorders and pregnancy related complications. Vitamin D hormone has important functions including immunomodulant, anti-inflammatory and anti-infective roles. It acts via monocyte and cell-mediated immunity stimulation, suppression of lymphocyte proliferation, antibody production and cytokine synthesis.